Schiff Base-Crosslinked Tetra-PEG-BSA Hydrogel: Design, Properties, and Multifunctional Functions - Yuanyuan Qu; Jinlong Li; Xin Jia; Lijun Yin (Journal of Functional Biomaterials)
Hydrogel network structures play a crucial role in determining mechanical properties and have broad applications in biomedical and industrial fields. Therefore, their rational design is essential. Herein, we developed a Schiff base-crosslinked hydrogel through the reaction of Tetra-armed polyethylene glycol with aldehyde end groups (Tetra-PEG-CHO) and bovine serum albumin (BSA) under alkaline conditions. In addition, the Tetra-PEG-BSA hydrogel showed a rapid gelation time of around 11 s, much faster than that of the GLU-BSA, HT-BSA, and GDL-BSA hydrogels. It had high optical transmittance (92.92% at 600 nm) and swelling ratios superior to the other gels in different solutions, maintaining structural integrity even in denaturing environments such as guanidine hydrochloride and SDS. Mechanical tests showed superior strain at break (84.12 ± 0.76%), rupture stress (28.64 ± 1.21 kPa), and energy dissipation ability (468.0 ± 34.9 kJ·m−3), surpassing all control group hydrogels. MTT cytotoxicity assays indicated that cell viability remained >80% at lower concentrations, confirming excellent biocompatibility. These findings suggest that Tetra-PEG-BSA hydrogels may serve as effective materials for drug delivery, tissue engineering, and 3D printing.